Marketing digital em pequenas empresas - SOUSA, Adriielle Cristina de; SOUZA, Bruna Rosa de (060, 2022)
O marketing digital possui diversas ferramentas para análise e divulgação de dados e informação, porém, com pouco conhecimento e investimento por parte da empresa, nada acontece. Empresas tem utilizado cada vez mais as redes sociais como ferramenta de marketing com objetivo de alcançar seus consumidores esse trabalho foi desenvolvido com objetivo de mostrar algumas características do consumidor com foco nas redes sociais com a finalidade de entender como o marketing digital influencia o consumidor. Foram utilizadas algumas ferramentas metodológicas como a pesquisa feita através de um formulário on-line a análise dos dados foi feita através da das respostas obtidas através dos formulários preenchidos pelos entrevistados os resultados permitiram chegar a uma conclusão responder à pergunta problema desse trabalho.

Small companies have doubts about applying digital marketing because the biggest mistake is thinking that they need a large internal team to carry out the work, or they think that digital marketing is only for large companies, but that is not how it works, one of the opportunities what the company loses is visibility, it helps to reach people around you who sometimes have never heard of your company. Another great positive factor is the reduction of costs, as digital marketing has forms of metrics such as: creating a banner and knowing how many people were impressed, how many people clicked on the banner, if it was responsible for any specific action, so you will understand which channel to invest more, or less, or stop investing. Digital marketing will also help with competitiveness because the algorithm will not look at the number of employees your competitor has to have more visibility or not, it will look at the strategies that both are taking to reach the desired audience.
Digital marketing in small businesses
Keywords: Vendas; Consumidor; Gestão e Negócios